FSP-DDF coupling model of LBM for the fluid flow and heat transfer in porous media. (5th July 2019) - Shao, Baoli; Wang, Shuyan; Tian, Ruichao; Qiao, Zhenxuan; Chen, Yujia; Sun, Qiji
Highlights: FSP and DDF coupling model of Lattice Boltzmann method is proposed. The FSP method can be adopted to construct porous media. The fluid flow and heat transfer in porous media are simulated by FSP-DDF model. The velocity fluctuation increases with the increase of Re in porous media. Abstract: Finite size particle method (FSP) and double distribution function (DDF) coupling model of lattice Boltzmann method is proposed for the fluid flow and heat transfer in porous media. In this model, one velocity distribution function is used to simulate the flow field and one temperature distribution function is employed to simulate temperature fields for both fluid and solid, where three parameters for relaxation time are used. The calculation cost is greatly reduced compared with the two temperature distribution functions. The FSP method is very convenient to construct porous media with spherical particles or other shaped particles, and it is very accurate to simulate fluid flow and heat transfer in porous media using FSP-DDF coupling model. To validate FSP-DDF coupling model, we predicted the drag coefficient of a static spherical particle in flow field to test the boundary condition of fluid and spherical particle, and the heat diffusion process around an isothermal hot sphere submerged in a cold fluid is obtained to confirm the thermal boundary condition between particle and fluid two phases. The above simulation results are in good agreement with the experimental data and simulation data in the literature. Finally, the processes of fluid flow and heat transfer of kerosene in porous media are investigated using the FSP-DDF coupling model, and the particles that make up porous media are divided into two types: constant temperature and variable temperature. Simulation results indicate that velocity fluctuation caused by porous media structure increases with the increase of Reynolds number, and the temperature and velocity vary depending on the structure of porous media and flow pattern. The effect of heat convection can be reduced by loading variable temperature particles in the flow channel under the same mass force.